2021
DOI: 10.20473/mgi.v16i1.53-61
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Percentage of Body Fat With Speed and Cardiorespiratory Endurance Among Futsal Athletes in Surabaya

Abstract: Futsal is one of the sport that begin to be popular in Indonesia. Physical condition in futsal is an important aspect because it directly aff ects athlete performance especially for speed and cardiorespiratory. One of the factor that aff ect physical condition is percentage of body fat. The purpose of this study is to analyze the correlation between percent body fat with physical condition of futsal athletes in Surabaya. This study was an observational analytic study with cross sectional design. The population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…A review of the literature revealed a positive but weak association between body fat percentage and 10-m sprint tests and a moderate positive relationship between body fat percentage and 30-m sprint tests in a study on football players [18]. Damayanti and Adriani reported a strong positive correlation between body fat percentage and 20-m sprint performance in futsal players [19]. In their study on football players, Cerrah et al determined that a moderate positive correlation existed between body fat percentage and 10-m and 30-m sprint performances while finding a strong positive relationship between body fat mass and 10-m and 30-m sprint tests [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature revealed a positive but weak association between body fat percentage and 10-m sprint tests and a moderate positive relationship between body fat percentage and 30-m sprint tests in a study on football players [18]. Damayanti and Adriani reported a strong positive correlation between body fat percentage and 20-m sprint performance in futsal players [19]. In their study on football players, Cerrah et al determined that a moderate positive correlation existed between body fat percentage and 10-m and 30-m sprint performances while finding a strong positive relationship between body fat mass and 10-m and 30-m sprint tests [20].…”
Section: Discussionmentioning
confidence: 99%
“…Body fat limits mobility and leads to a decline in performance; therefore, a high level of body fat would be expected 01 01 51 to negatively affect speed and jumping ability. As a result, athletes with low body fat percentages can perform better than athletes with higher body fat levels [19].…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that the reduction in body mass, percent body fat, fat mass among the volunteers of experimental group might be due to the training. The reduction in body fat might be because of increase aerobic endurance exercise which is responsible for grater utilization of fat for energetic process (Damayanti & Adriani, 2021;Manna et al, 2010). The reduction in body mass and BMI may be due to reduction in of body fat after training (Manna et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The PS is an appropriate phase for improving player's body composition [ 63 ]. Recent studies showed that low body fat percentage in soccer (depending on each field position) is important for maximizing sprint [ 64 66 ], high-speed running distance [ 65 , 67 ], vertical jump [ 68 ], and aerobic fitness performance in soccer players [ 65 , 66 , 69 ]. Our results revealed significant decreases of body composition measurements.…”
Section: Discussionmentioning
confidence: 99%